The deferral and relapse`s time post induction chemotherapy in children with acute lymphoblastic leukemia at a National Hospital in Lambayeque - Tafur-Hoyos, Brenda Aurora Dolores (2022)
Objetive: To know the delay and relapse time after induction chemotherapy in children with acute lymphoblastic leukemia (ALL) in a national hospital in Lambayeque. The study: Analytical observational study of a retrospective cohort. The medical records of patients whose age is 2 and 15 years with diagnosis of ALL who achieved complete remission at the end of induction treated and a national hospital in Lambayeque ,were reviewed. Findings: The patients studied had a median age of 5 years. Although the majority responded at the end of IA induction, still 43/75 children with ALL relapsed. Children with relapse had a delay of 6 days [IQR: 0-25] between the end of induction and the beginning of the consolidation phase. Conclusion: Delay ≥7 days in chemotherapy regimens affects the sustainability of remission.